2022
DOI: 10.3389/fmed.2022.818144
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides Prevent and Dissolve Cholesterol Gallstones by Modulating the Homeostasis of Cholesterol and Bile Acids

Abstract: Gypenosides (GPs), obtained from Gynostemma pentaphyllum (Thunb.) Makino, have been traditionally prescribed to treat metabolic disorders in Asians. This study assessed whether GPs could prevent lithogenic diet (LD)-induced cholesterol gallstone (CG) formation and enhance CG dissolution in mice. Gallstone-susceptible C57BL/6J mice were fed an LD or normal chow, with or without GPs. Bile acids (BAs) in gallbladder bile were analyzed by liquid chromatography-tandem mass spectrometry. Differentially expressed hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The intersection of the serum and liver metabolites revealed several potential therapeutic targets. Furthermore, KEGG functional analysis showed that ABC transporters and bile secretion were closely associated with CGS, previous microbiota and metabolism results, and other relevant studies ( Figueira-Mansur et al, 2020 ; Ye et al, 2021 ; Ye et al, 2022 ; Zhuang et al, 2022 ). In our study, obacunone was the most common active metabolite in the serum, liver, and gallbladder.…”
Section: Discussionmentioning
confidence: 55%
“…The intersection of the serum and liver metabolites revealed several potential therapeutic targets. Furthermore, KEGG functional analysis showed that ABC transporters and bile secretion were closely associated with CGS, previous microbiota and metabolism results, and other relevant studies ( Figueira-Mansur et al, 2020 ; Ye et al, 2021 ; Ye et al, 2022 ; Zhuang et al, 2022 ). In our study, obacunone was the most common active metabolite in the serum, liver, and gallbladder.…”
Section: Discussionmentioning
confidence: 55%
“…Gypenoside is the main component of Gynostemma pentaphyllum (Thunb.) Makino [ 33 , 34 ], and exist mainly as dammarane type-triterpene glycosides [ 35 ]. In an oxygen–glucose deprivation/reperfusion (OGD/R) cell and MIRI rat models, gypenoside treatment ameliorated impairments in cardiac morphology at a dose of 50 mg/kg, 100 mg/kg, and 200 mg/kg [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, G. pentaphyllum is a plant with the same origin as medicine and food. G. pentaphyllum has many functions such as liver protection, anti-tumor, anti-inflammation, and balancing blood sugar and blood lipids 6 10 that is often made into G. pentaphyllum tea edible.…”
Section: Introductionmentioning
confidence: 99%